Analisis Disiplin Aparatur Sipil Negara pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kabupaten Aceh Timur - Muzanny, Muzanny; Siregar, Nina Siti Salmaniah; Isnaini, Isnaini (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2019)
The purpose of this research is to analyze the discipline of the State Civil Apparatus at the Human Resources Development and Human Resources Development Agency in East Aceh Regency in terms of time discipline and work discipline and what are the obstacles. While the purpose of this study is to analyze the time discipline and work discipline of the state civil apparatus at the Human Resources and Human Resources Development Agency in East Aceh District and determine what obstacles are faced in improving the time discipline and work discipline of the state civil apparatus. The research method used is descriptive qualitative method, with a focus of research that is time discipline and work discipline. Based on the results of research and discussion the authors conclude that time discipline and work discipline apparatus BKPSDM East Aceh in general is good. Barriers that occur are distant domicile, do not have standard work standards, lack of maximum vigilance, not all understand work ethics. Some things suggested are more cooperative, give penalties for violations, continuous supervision.